A novel small molecule TLR4 antagonist (IAXO-102) negatively regulates non-hematopoietic toll like receptor 4 signalling and inhibits aortic aneurysms development. Issue 2 (October 2015) - Huggins, Christopher; Pearce, Stuart; Peri, Francesco; Neumann, Frank; Cockerill, Gillian; Pirianov, Grisha
Abstract Objectives The toll-like receptors (TLRs), including TLR4, have been shown to play a crucial role in vascular inflammatory diseases, such as atherosclerosis and aneurysm. The main goal of this study was to determine the potential of IAXO-102 (Innaxon, Tewkesbury), a novel small molecule TLR4 antagonist, to modulate non-hematopoietic TLR4 proinflammatory signalling and inhibit experimental abdominal aortic aneurysm (AAA) development. Methods Human umbilical vein endothelial cells (HUVEC) and Angiotensin II-induced experimental AAA development were our in vitro and in vivo models respectively. Western blotting, antibody array and ELISA approaches were used to explore the effect of IAXO-102 on TLR4 functional activity on two levels: modulation of TLR4-induced mitogen activated protein kinases (MAPK) and p65 NF-kB phosphorylation and expression of TLR4 dependent proinflammatory proteins. Results Following activation of TLR4, in vitro/in vivo data revealed that IAXO-102 inhibited MAPK and p65 NF-kB phosphorylation associated with down regulation of the expression of TLR4 and TLR4 dependent proinflammatory proteins. Furthermore, IAXO-102 decreased Angiotensin II-induced aortic expansion, rupture and incidence of AAA. Conclusions These results demonstrate the ability of IAXO-102 to negatively regulate TLR4 signalling and to inhibit experimental AAA development, suggesting the potential therapeutic use of this TLR4 antagonist for pharmacological intervention of AAA.